Keanekaragaman Marchantiophyta Epifit Zona Montana di Kawasan Gunung Ungaran, Jawa Tengah - Aristria, Desy; Perwati, Lilih Khotim; Wiryani, Erry (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Bryophytes consisting of three division, there are Bryophyta (mosses), Marchantiophyta (liverworts) dan Anthocerotophyta (hornworts). Marchantiophyta are divided in two types, leafy liverworts and thallose liverworts. Mount Ungaran which has many diversity of Bryophytes but research about Bryophytes in this area are sparse. The aim of this research was to observe diversity of Marchantiophyta on tree trunks in montane zone (altitudes 1300 to 2050 meters above sea level). Sampling was conducted in April and May 2012 at three different altitudes ( 1355, 1660, and 2040 meters above sea level). Identification of Bryophytes was carried out at Laboratorium of Ecology and Biosistematics, Department Biology, Faculty of Science and Mathematics, Diponegoro University, Semarang, Indonesia. The results shown there are 9 families with 26 species belonging to the division Marchantiophyta. Â Keywords: Epiphytic Marchantiophyta, Mount Ungaran, diversity, montana zone.